Coexpression of MCT1 and MCT4 in ALK-positive Anaplastic Large Cell Lymphoma: Diagnostic and Therapeutic Implications. (7th October 2021) - Choi, Jung-Woo; Lee, Youngseok; Kim, Hyunchul; Cho, Hyun Yee; Min, Soo Kee; Kim, Young-Sik
Abstract : Supplemental Digital Content is available in the text. Abstract : In solid tumors, glycolytic cancer or stromal cells export lactates through monocarboxylate transporter (MCT) 4, while oxidative cancer or stromal cells take up lactates as metabolic fuels or signaling molecules through MCT1. CD147 acts as a chaperone of MCT1 or MCT4. Unlike solid tumors, malignant lymphomas have a peculiar tumor microenvironment. To investigate the metabolic phenotype of malignant lymphoma associated with lactate transport, we analyzed immunohistochemical expressions of MCT1, MCT4, and CD147 in 247 cases of various malignant lymphomas. Surprisingly, both MCT1 and MCT4 were diffusely expressed on tumor cell membranes in all cases (11/11, 100%) of anaplastic lymphoma kinase (ALK) (+) anaplastic large cell lymphoma (ALCL). In contrast, only MCT1 was diffusely expressed in tumor cells of ALK(−) ALCL, as well as in B-cell, natural killer/T-cell, T-cell, and classic Hodgkin lymphomas. In these lymphomas, MCT4 expression was mostly localized to adjacent stromal cells. The pattern of diffuse membranous MCT1 and partial MCT4 expressions in tumor cells was observed in 1 case each of peripheral T-cell lymphoma (1/15, 6.7%) and multiple myeloma (1/34, 2.9%). CD147 was diffusely expressed in all types of lymphoma tumor and/or stromal cells. In conclusion, ALK(+) ALCL has a unique metabolism showing high coexpression of MCT1 and MCT4 in tumor cells. Because only ALK(+) ALCL overexpresses MCT4, immunostaining for MCT4 together with ALK is very useful for differential diagnosis from ALK(−) ALCL or peripheral T-cell lymphoma. Moreover, dual targeting against MCT1 and MCT4 would be an appropriate therapeutic approach for ALK(+) ALCL.